Quantitative and qualitative study of industrial dust fall in Yazd (case study of steel industry in Yazd) - mostafa abyareh; Farhad Nejadkoorki; mohammad reza ekhtesasi; mohammad akhavan ghalibaf (Mashhad University of Medical Sciences, 2019)
Abstract Backound and purpose: The communities have been faced the environmental challenges by dust particles as an important part of air pollution that are emitted into the atmosphere every day by chimney of factories and power plants out. The aim of this study was to determine the quality and quantity of industrial dust around the Yazd Steel Company to control and supervise the industrial dust to make the better environmental condition.   Materials and Methods: In this study, according to the wind direction, the falling dust particles, were collected and weighted in two sediment stations before and after the company from 1/2/2016 to 30/4/2016. The sampling was done by MDCO. Then, the taken samples transferred to an elemental analysis laboratory, and the amounts of dust-forming elements were measured by XRF device. Results. Based on the obtained results, the maximum and minimum levels of the concentrations of falling dust particles were 32.9g/m2 on March for,0.0014 g/m2 on February for SiO2 and SrO respectively. the major elements and chemical compounds of dust included: SiO2، CaO، CO2، Al2O3، MgO، Fe2O3، K2O، Na2O، SO3، TiO2، Cl، P2O5، MnO، ZnO، Pt، Au، SrO. .   Conclusions: The results of statistical tests demonstrated that there was a significant difference between the amounts of these elements before and after the company. Therefore, proper management and more accurate monitoring are necessary to protect the environment in this industry